Description of Distolabrellus magnivulvatus sp. n. (Nematoda, Rhabditida, Mesorhabditidae) from Iberian peninsula, the second species of a rare genus - Abolafia, Joaquín; Peña-Santiago, Reyes (Zootaxa, 2011)
Distolabrellus magnivulvatus sp. n., collected from green-house soil in central Iberian peninsula, is described and illustrated. It is characterized by having 0.89–1.07 mm long body in females and 0.65–0.99 mm in males, cuticle tesselated, lateral fields with three longitudinal incisures, lip region almost continuous and 10–13 µm wide, lips dimorphic (alternately extremely reduced and ovoid), stoma 22–30 μm long or 2.0–2.8 times lip region diameter, pharyngeal collar shorter than half of total stoma length, distance to pharyngo-intestinal junction 148–190 µm, V = 82–86, vulva a transverse slit located in a vulval cone and with its anterior lip bearing a flap-like structure, body cuticle surrounding the vulva especially differentiated, female tail conical with acute tip (68–90 μm, c = 10.9–14.6, c’ = 2.1–4.5), male tail conical (23–32 μm, c = 24.8–34.0; c’ = 1.0–1.4), bursa peloderan and open anteriorly, genital papillae ten pairs (2+1/4+3), spicules 54–64 μ m long and fused two-thirds, and gubernaculum 32–41 μm long. The new taxon is the second species of the genus Distolabrellus and is compared to type species D. veechi.